Penerapan Metode SEM-PLS pada Kepuasan Pengguna Aplikasi Instagram - Tamba, Felicia Joy Rotua; Nasywa, Syarifah; Salsabila, Adellia; Khoiruddin, Ahmad Zulfikar; Tandi Kala, Ezra Alfrianto; Sifriyani, Sifriyani; Sari, Nariza Wanti Wulan; Yuniarti, Desi; Nadhilah Widyaningrum, Erlyne; Atarezcha Pangruruk, Thesya (Program Studi Statistika FMIPA Universitas Mulawarman, 2025)
Social media platforms, particularly Instagram, have emerged as widely utilized channels among diverse user groups, including university students, for information sharing, social interaction, and entertainment purposes. The study seeks to analyze how Instagram quality, perceived benefits, and social interaction contribute to user satisfaction and loyalty within the FMIPA community at Mulawarman University. The SmartPLS 3.0 software facilitates the use of the Structural Equation Modelling technique based on Partial Least Squares (SEM-PLS) in this investigation. The results show that each of the three independent factors significantly and favourably affects user pleasure, which in turn significantly boosts customer loyalty. The R-square values of 0.685 for satisfaction and 0.655 for loyalty suggest that the proposed model adequately explains the relationships among the variables. Furthermore, all measurement indicators were confirmed to be both valid and reliable. In conclusion, the study demonstrates that users’ positive perceptions of Instagram’s quality, benefits, and social interaction contribute to enhanced satisfaction and foster greater loyalty toward the platform.